Local Goverment Accountability in the Lens of Women Community in Malaysia (Journal of Governance and Development (JGD), 2017)
This study was designed to examine women participation to determine the level of accountability delivered by staffs and councillors in Malaysian local government. Survey method was used for the study and a sample of three hundred eighty five (385) women were randomly selected from the entire population of women that frequently were dealing with local government administration, especially involved in activities organised by local government. Twenty-items questionnaires were adopted from previous measurement to gain the relevant data. Data collected were analysed using frequency and percentage distribution. The results of the study revealed that women citizens were satisfied with the execution of local government accountability and responsibility. This satisfaction level is seen to rise in recent years because of performance of each local government in Malaysia being monitored and evaluated each year using star rating system. The evaluations assessed all functions of local government including public services. Therefore, local governments are always enhancing their services to meet the requirements of star rating.